2021
DOI: 10.2147/copd.s331154
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Omega-3 Fatty Acids on Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Purpose Omega-3 fatty acid is an emerging hotspot on anti-inflammation and chronic obstructive pulmonary disease (COPD) is known as a chronic inflammatory disease. The effect of Omega-3 fatty acid supplement on patients with COPD remains mixed for insufficient evidence. This systematic review and meta-analysis is based on neat randomized controlled trials trying to give a clearer impression on the effect of Omega-3 on patients with COPD. Methods This systematic review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 42 publications
(68 reference statements)
0
15
0
Order By: Relevance
“…Nutritional status is particularly important because in the chronic progressive course of COPD, malnutrition impairs quality of life, increases the number and risk of exacerbations, length of hospital stay and health care costs, and low BMI is an independent risk factor for mortality (31)(32)(33). Several previous studies have shown that the intake of PUFAs improves the quality of life of patients (15)(16)(17)(18)(19)(34)(35)(36)(37)(38), as COPD is a respiratory and systemic inflammatory disease (36). Omega-3 can slow the inflammatory process and improve quality of life (34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional status is particularly important because in the chronic progressive course of COPD, malnutrition impairs quality of life, increases the number and risk of exacerbations, length of hospital stay and health care costs, and low BMI is an independent risk factor for mortality (31)(32)(33). Several previous studies have shown that the intake of PUFAs improves the quality of life of patients (15)(16)(17)(18)(19)(34)(35)(36)(37)(38), as COPD is a respiratory and systemic inflammatory disease (36). Omega-3 can slow the inflammatory process and improve quality of life (34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown that the intake of PUFAs improves the quality of life of patients (15)(16)(17)(18)(19)(34)(35)(36)(37)(38), as COPD is a respiratory and systemic inflammatory disease (36). Omega-3 can slow the inflammatory process and improve quality of life (34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…16 In another meta-analysis including eight RCTs and 418 patients, researchers found that omega-3 intake was associated with IL-6 reduction in COPD patients. 137 Omega-3 supplementation's effects on immune responses are debatable at various levels, ranging from 2500 mg/d to higher doses of 4800 mg/d (Table 1). [130][131][132][133][134][135][136]…”
Section: Omega-3 and Pro-inflammatory/ Inflammatory Cytokinesmentioning
confidence: 99%
“…In this case, adequate dietary intake of ω-3 PUFAs can be considered as a protective factor against the deterioration of lung function in smokers and the progression of COPD. Consumption of ω-3 PUFAs by COPD patients may be associated with weight gain and lower IL-6 levels compared with placebo [ 262 ].…”
Section: The Importance Of Nutrition In the Progression Of Copdmentioning
confidence: 99%